Clinical features and evaluation of Quality of life in children with CKD. (Eurasian Medical Research Periodical, 2022)
This paper aimed to assess the quality of life for children between the ages of 8 to 15 years in Iraq KIDSCREN-52 dimensions and outcomes were collected for pediatric patients from different hospitals with the period from 2019 to 2020. In this study, the results were analyzed using IBM SPSS SOFT 22. statistical analysis program Where a questionnaire was distributed to parents or first-degree relatives to diagnose the condition of the children and evaluate the psychometric characteristics